Development of Pandemic Burnout Inventory for Health Personnel - Phuspa, Sisca Mayang; Dharmastuti, Anjarie; Sutomo, Adi Heru; Alim, Syahirul (UI Scholars Hub, 2023)
The COVID-19 pandemic has increased the workload of health personnel in Indonesia, and the risk of burnout has thus doubled. Several instruments exist to assess burnout, but none have been specifically developed for health personnel during the COVID-19 pandemic. Therefore, to close this gap, developing a Pandemic Burnout Inventory for health personnel is important. This study used mixed methods with a sequential exploratory design at five COVID-19 referral hospitals. A total of 30 informants were employed in the qualitative phase, selected using an intensity sampling approach, and 731 respondents in the quantitative phase were obtained in field trials and online questionnaires. Finally, a Pandemic Burnout Inventory was formed with 14 items. The content validity, based on expert judgment, showed very good results. The assessment of item discrimination and construct validity showed good results. The concurrent validity and reliability of the instrument showed fairly good results. In general, the Pandemic Burnout Inventory meets the criteria for a good instrument according to psychometrics: it is objective, standard, valid, and practical. Health care institutions can use this instrument to evaluate and prevent the deterioration of the mental health condition of health personnel handling COVID-19 or similar health crises.